A family of hexanuclear lanthanide complexes with slow magnetic relaxation for Dy6 cluster. (17th June 2017) - Wu, Li-Juan; Yang, Hua; Zeng, Su-Yuan; Li, Da-Cheng; Dou, Jian-Min
Graphical abstract: Five isostructural hexanuclear lanthanide complexes [Ln6 (L)4 ( μ 3 -OH)4 (CH3 OH)2 (NO3 )2 ] (Ln = Gd (1 ), Tb (2 ), Dy (3 ), Ho (4 ), Er (5 )) based on 1, 3-bis(4-methoxysalicylideneamino)-2-propanol (H3 L) have been synthesized and characterized. Each structure contains a Ln6 O6 core with two trinuclear subunits fused together through μ 3 -O atoms. The magnetic properties reveal slow relaxation of magnetization in complex3 . Abstract: A family of isostructural, hexanuclear lanthanide complexes [Ln6 (L)4 ( μ 3 -OH)4 (CH3 OH)2 (NO3 )2 ] (Ln = Gd (1 ), Tb (2 ), Dy (3 ), Ho (4 ), Er (5 ), H3 L = 1, 3-bis(4-methoxysalicylideneamino)-2-propanol) were obtained by the reactions of Ln(NO3 )3 with the selective ligand. Complexes1 –5 were characterized by X-ray single crystal diffraction, IR spectra, and powder X-ray diffraction analyse. The molecule structure of these complexes contains a Ln6 O6 core ligated by two trinuclear subunits. Direct-current (dc) magnetic susceptibility studies reveal the antiferromagnetic interactions between Lanthanide ions. The in-phase ( χ ′) and out-of-phase ( χ ″) signals have been observed below 10 K in complex3, indicating slow relaxation of the magnetization. The deduced effective energy barrier ( U eff / k B ) and relaxation time ( τ 0 ) are 6.17 K and =4.9 × 10 −5 s, respectively.